Efeito do uso do mapa da empatia em saúde durante o atendimento ambulatorial em uma residência médica de ortopedia - Cançado, Paula Vilaça Ribeiro (2020)
Introduction: Empathy is one of the domains of emotional intelligence, and its practice is connected to better diagnostic and therapeutic results. In despite of its importance, it has been observed that this ability is prone to decrease during the medical training. The pedagogical methods for teaching and practicing empathy over the period that physicians are trained have been widely discussed. The Health Empathy Map (HEM) is a structured instrument that enables the practice of this skill in a health care environment. Objectives: Assess the effectiveness of the use of HEM as empathy skill practice method on the scores of empathy of the orthopedics and traumatology resident physicians and also the patients perception of empathy. Materials and Methods: Experiential study, carried out by 22 orthopaedics and traumatology resident physicians at São Francisco Hospital Complex. In the first phase, the empathy of resident physicians was assessed using the Jefferson Scale of Medical Empathy (JSE), and in the patients seen in the first-aid room, the Consultation and Relational Empathy (CARE) instrument was applied in order to assess the empathy based on the patient perspective. Sociodemographic questionnaires were applied together to characterize residents and patients. In the second phase, the implementation of the use of HEM was carried out by the resident in the outpatient service for four weeks. One week after the interruption of the use of MES (3rd phase), JSE and CARE were again applied. Results: The statistics analysis by the student´s t-test showed that the empathy scores of JSE did not show significant differences between the first and the third phases. Furthermore, the chi-squared test demonstrated that the intervention was not enough to increase the self-perception of residents level of empathy. When the patients perception of empathy is assessed, the comparison of the scores from the CARE scale by the student´s t-test, showed an increase of these scores between the first and third phases, showing an improvement of empathy perceived by the patient. The Pearson analysis of correlation revealed that there is no dependence between the results of these two scales. Conclusion: The HEM, for four weeks, did not produce an increase on the scores of self-report of the resident physicians empathy. Notwithstanding, after the use of HEM there have been an increase in the perception of the resident physician empathy during the medical care from the patients point of view. There was no correlation between the in-training physicians empathy self-assessment and their patients assessment. From the patient’s viewpoint, there was an improvement of the resident’s empathy after the intervention, demonstrating that an empathic behaviour can be taught integrating the training and the HEM use in the Medical Residency Programmes